Protesting During a Pandemic: Narratives on Risk Taking and Motivation to Participating in the 2020 March on Washington. (July 2021) - Cobbina, Jennifer; LaCourse, Ashleigh; Brooke, Erika J.; Chaudhuri, Soma
The study elucidates the interplay of COVID-19 and the wave of Black Lives Matter protests to assess motivation and risk taking for protest participation. We draw on protesters' accounts to examine how police violence influenced the participants decision making to participate in the 2020 March on Washington during a pandemic that exacerbated the risks already in place from protesting the police. We found that protesters' social position and commitment to the cause provided motivations, along with a zeal to do more especially among White protesters. For Black participants, the images in the media resonated with their own experiences of structural racism from police.